New conceptual model of Reverse Logistics of a worldwide Fashion Company - Pereira, Maria Teresa Ribeiro (2020)
This paper focuses on the logistics activity of the Outlet Retail industry of accessories and clothing items produced by a Portuguese fashion company, operated by an also Portuguese Third-Party Logistics providers (3PL). The main goal of this study is to address and analyze the current business and process model used by the Portuguese 3PL, to compare it with other existing models within the state-of-art, and to design a new conceptual model for 3PL’s reverse logistics activities in the Clothing and Fashion Industry. The second main goal is to identify improvement opportunities, while observing and mapping logistic activities, in order to increase productivity, reduce costs, and improve the quality of the service. The analysis was supported by Lean and Supply Chain methodologies and by appropriate tools like the Value Stream Mapping (VSM). VSM contributed to map the business processes in a structured and systematic way and provided a wide perception of the value chain to identify the waste that could be reduced. The data used to feed the VSM was collected by cycle time measurements and also data analytics. After the analysis, a new Value Stream Proposal was presented for that business model, as well as the gains achieved by the execution of technologic and lean-based improvement actions. Finally, this paper presents a Conceptual Business Model for 3PL’s Reverse Logistics in the Clothing and Fashion Industry.